1989
DOI: 10.1126/science.2555923
|View full text |Cite
|
Sign up to set email alerts
|

A Formalin-Inactivated Whole SIV Vaccine Confers Protection in Macaques

Abstract: A vaccine against human immunodeficiency virus (HIV) would be highly effective in stopping the acquired immunodeficiency syndrome (AIDS) epidemic. A comprehensive evaluation of potential vaccine methodologies can be made by means of the simian model for AIDS, which takes advantage of the similarities in viral composition and disease potential between simian immunodeficiency virus (SIV) infection of rhesus macaques and HIV infection in humans. Immunization with a formalin-inactivated whole SIV vaccine potentiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
165
3
3

Year Published

1992
1992
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 394 publications
(179 citation statements)
references
References 27 publications
8
165
3
3
Order By: Relevance
“…Schnittman et al (1990) suggested that the decline ofCD29+ cells in HIV positive individuals was due to the preferential replication of HIV in these cells. A very early loss ofCD29+CD4+ cells from the blood ofSIVsm infected macaques has also been noted by Murphey-Corb et al (1989). The low level of CD29+CD8+ cells in blood and spleen ofthe animal sacrificed 6 weeks post infection was not seen in the other monkeys at later times.…”
Section: Discussionmentioning
confidence: 60%
“…Schnittman et al (1990) suggested that the decline ofCD29+ cells in HIV positive individuals was due to the preferential replication of HIV in these cells. A very early loss ofCD29+CD4+ cells from the blood ofSIVsm infected macaques has also been noted by Murphey-Corb et al (1989). The low level of CD29+CD8+ cells in blood and spleen ofthe animal sacrificed 6 weeks post infection was not seen in the other monkeys at later times.…”
Section: Discussionmentioning
confidence: 60%
“…In the past three decades, a large literature has demonstrated that muramyl peptides display a number of antiviral activities in vitro and in vivo, against microbes such as influenza, herpes simplex or human immunodeficiency viruses [29][30][31]. However, the mechanisms by which these muramyl peptides display antiviral properties remain poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…simian acquired immune deficiency syndrome (52). SIV (53) , and a recombinant HIV-1 vaccine in chimpanzees (54). In the absence of an efficacious adjuvant, little or no protection is observed.…”
Section: Use Of Adjuvants In Vaccinesmentioning
confidence: 99%